2021
DOI: 10.1101/2021.08.01.454635
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-fidelity, high-spatial-resolution diffusion MRI of the ex-vivo whole human brain on the 3T Connectom scanner using structured low-rank EPI ghost correction

Abstract: Diffusion MRI (dMRI) of whole, intact, fixed postmortem human brain at high spatial resolution serves as key bridging technology for 3D mapping of structural connectivity and tissue microstructure at the mesoscopic scale. Ex vivo dMRI offers superior spatial resolution compared to in vivo dMRI but comes with its own technical challenges due to the significantly reduced T2 relaxation times and decreased diffusivity incurred by tissue fixation. The altered physical properties of fixed tissue necessitate the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…Previous work has shown that eddy currents in high‐gradient dMRI can be long‐lasting and persist beyond the EPI readout 28 . These effects are exacerbated in segmented acquisitions and can result in strong geometric distortions and ghosting artifacts that vary with the diffusion‐encoding direction 24,25,29–33 . Current methods that can correct ghosting artifacts with conventional gradient strengths 34,35 underperform for diffusion‐weighted (DW) multi‐shot EPI experiments using strong diffusion‐sensitizing gradients due to the complex nonlinear spatiotemporal magnetic field evolution incurred by the induced eddy currents 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that eddy currents in high‐gradient dMRI can be long‐lasting and persist beyond the EPI readout 28 . These effects are exacerbated in segmented acquisitions and can result in strong geometric distortions and ghosting artifacts that vary with the diffusion‐encoding direction 24,25,29–33 . Current methods that can correct ghosting artifacts with conventional gradient strengths 34,35 underperform for diffusion‐weighted (DW) multi‐shot EPI experiments using strong diffusion‐sensitizing gradients due to the complex nonlinear spatiotemporal magnetic field evolution incurred by the induced eddy currents 36 .…”
Section: Introductionmentioning
confidence: 99%